PENGARUH MANAJEMEN KESISWAAN TERHADAP PEMBINAAN BUDAYA RELIGIUS UNTUK MEWUJUDKAN PRESTASI BELAJAR SISWA - Al Firdaus, Akbar; Geusan Akbar, Gugun; Anisa Larasati, Retno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of student management on the development of religious culture and its implications for students’ learning achievement at SDIT Garut Islamic School Prima Insani. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 52 teachers and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS. The results indicate that student management has a positive and significant effect on religious culture development and students’ learning achievement. Furthermore, religious culture development also has a positive and significant effect on students’ learning achievement. Mediation analysis reveals that religious culture development partially mediates the relationship between student management and students’ learning achievement. These findings emphasize the importance of integrating effective student management with religious culture development as a strategic approach to enhancing students’ learning achievement holistically